Pengaruh Marketing Public Relation Terhadap Loyalitas Konsumen di Holly Mart Bima - Rangga Kautsar Triananda; Ismunandar; Muhajirin (Indo Publishing, 2025)
This study aims to examine the influence of Marketing Public Relations on Consumer Loyalty at Holly Mart Bima. The research method used in this study is associative. The population used was all consumers who had shopped at Holly Mart Bima, with an unknown population, and a required sample size of 96 respondents. The results showed that Marketing Public Relations has a positive and significant influence on consumer loyalty at Holly Mart Bima. Future researchers are expected to expand the research by adding other variables that can influence consumer loyalty, including service quality, product quality, and others. Furthermore, Holly Mart Bima is advised to improve its marketing public relations program to increase consumer loyalty in the future.